1995
DOI: 10.1002/ajmg.1320600509
|View full text |Cite
|
Sign up to set email alerts
|

Systematic screening for mutations in the promoter and the coding region of the 5‐HT1A gene

Abstract: In the present study we sought to identify genetic variation in the 5-HT1A receptor gene which through alteration of protein function or level of expression might contribute to the genetic predisposition to neuropsychiatric diseases. Genomic DNA samples from 159 unrelated subjects (including 45 schizophrenic, 46 bipolar affective, and 43 patients with Tourette's syndrome, as well as 25 healthy controls) were investigated by single-strand conformation analysis. Overlapping PCR (polymerase chain reaction) fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 25 publications
1
26
1
Order By: Relevance
“…Several HTR1A polymorphisms have been identified, but many are too rare to assess their association with mental illness [105][106][107][108][109]. In a preliminary report we identified a common C(-1019)G 5-HT1A polymorphism [110] that is identical to the site reported as C(-1018)G [108].…”
Section: -Ht1a Promoter Polymorphisms and Mental Illnessmentioning
confidence: 75%
“…Several HTR1A polymorphisms have been identified, but many are too rare to assess their association with mental illness [105][106][107][108][109]. In a preliminary report we identified a common C(-1019)G 5-HT1A polymorphism [110] that is identical to the site reported as C(-1018)G [108].…”
Section: -Ht1a Promoter Polymorphisms and Mental Illnessmentioning
confidence: 75%
“…Example of simultaneous genotyping of 13 serotonin polymorphisms using PCR-SSP. One DNA sample has been subjected to the 26 PCR-SSP reactions in the order listed in Table I [Comings et al., 1996] [Comings et al., 1996 Asn/His 4 0.04 His 12 0.06 0.06 [Comings et al., 1996 [Nielsen et al., 1997]; tryptophan dioxygenase (codon 748 Asn/His) [Comings et al., 1996]; monoamine oxidase A (codon 941 g/t, and codon 1460 c/t) [Hotamisligil and Breakefield, 1991]; and the serotonin receptors: 5HT1A receptor (codon 28 Thr/Asn) [Erdmann et al., 1995;Nakhai et al., 1995]; 5HT1Da receptor (codon 450 t/c) ; 5HT1Db receptor (codon 287 g/c) [Sidenberg et al., 1993]; 5HT2A receptor (codon 25 Thr/Asn, codon 102 t/c, codon 452 His/Tyr) [Erdmann et al., 1996;Warren et al., 1993]; 5HT2C receptor codon 23 Cys/Ser) ; and 5HT5A (nucleotide −19 g/c) [Shimron-Abarbanell et al., 1997]. Allele and haplotype frequencies are shown in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…The Ser22 variant was found only in a Finnish population sample at a frequency of 0.2%, whereas the Val28 variant was identified at a higher frequency (0.55%) and in different populations (Nakhai et al 1995;Bergen et al 1996). Erdmann et al (1995) have also observed Val28 among patients affected by schizophrenia, bipolar affective disorder, and Tourette's syndrome, but found no difference in frequency between patients and controls. Interestingly, another naturally occurring polymorphism of the 5-HT 1A receptor has been recently described in the putative amino-terminal extracellular domain of the receptor at amino acid 16 (proline to leucine) in a Japanese population sample (Harada et al 1996).…”
mentioning
confidence: 83%